Letter (copy) : Goods for Northern Spain by S.S. "Marian Moller" - Bell, Ernest A.
029-0106-001 EAB/985 INTERNATIONAL. 4th August 1937. Mr. E. Winstanley, Export Department, Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER 4. Dear Mr. Winstanley, GOODS FOR NORTHERN SPAIN BY s.s. "MARIAN MOLLER". We have deferred replying to your letter of the 7th July (Your ref: Export/ST/MM.9165) pending receipt of an official intimation that the s.s. "SIL" had sailed for Gijon, but we now learn that all the goods set out in your invoices Nos. 36/1955 and 36/1953 were shipped on the "MARIAN MOLLER". We agree the amounts included in your statement dated 7 July, i.e. £262. 4. 0., with the exception that you do not appear to have taken into consideration the amount of £10.11.6 for insurance charges as set out on your invoice No. 36/2113. If you will be good enough to let us have an amended statement we will let you have our cheque by return. With regard to your statement dated 8 July for £42. 7. 0., we shall be glad to have a detailed account from you, as we are at a loss to understand to what this charge refers. Yours sincerely, International Department. 292/946/29/106